Gdańsk - Lelewicz, Kazimierz (1896-1986). (Gdańsk - Wrzeszcz, 1947)
Przedstawia ruiny kościoła św. Barbary w Gdańsku.
Tyt. i data ołówkiem na rewersie.
Keywords: Fotografie -- Polska -- Gdańsk; Gdańsk (Polska) -- 1945-1970 -- fotografie